ФІНАНСОВИЙ КОНТРОЛЬ НА МІСЦЕВОМУ РІВНІ ЯК ДІЄВИЙ ІНСТРУМЕНТ ПІДВИЩЕННЯ ЕФЕКТИВНОСТІ БЮДЖЕТНОЇ СИСТЕМИ - Легкоступ, Ігор; Мартинюк, Анна (Технодрук, 2021)
This article reveals the need for financial control at the local level as an effective tool for improving the efficiency of the budget system. This is due to the fact that financial and material resources are concentrated in a particular area, region or locality. Economists pay a lot of attention to the study of the processes of allocation and use of these resources, provide recommendations for change and reform. to increase the effectiveness of the financial control system at the local level in Ukraine, it is necessary to review and analyze the theoretical basis and practical provisions. The urgency of the work lies in the need for research and development of scientifically sound recommendations for further development of the control system at the local level. The purpose of the article is to study the problems of insufficient efficiency of state financial control over local budgets and find ways to improve it.
Keywords: фінансовий контроль; бюджетна система; бюджетна децентралізація